EVALUASI KINERJA KEUANGAN DAERAH PROVINSI SUMATERA UTARA PERIODE TAHUN 2009 s/d 2016 (EVALUATION OF FINANCIAL PERFORMANCE OF NORTH SUMATRA PROVINCE PERIOD OF 2009 TO 2016) - Porman Juanda Marpomari Mahulae (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
This study aims to describe the financial performance of the region of North Sumatra Province period 2007 to 2016, and to evaluate by assessing the impact or influence of financial performance on macroeconomic variables and community welfare. In general, this research uses quantitative approach. In this study researchers used quantitative descriptive (using financial ratio formulas) and multiple linear regression to conduct path analysis of research variables. Based on the calculation of regional financial ratios to the North Sumatera Provincial Government Budget Realization Report for the period of 2009 to 2016 it is known that: 1) The financial independence ratio of North Sumatera Provincial Government is in high criteria with an average self-reliance ratio of 157.06%; 2) The effectiveness ratio of regional finance of North Sumatera Provincial Government is on the criteria is quite effective with the value of the average effectiveness ratio of 95.41%; 3) The financial efficiency ratio of North Sumatera Provincial Government is on the criteria is quite efficient with an average efficiency ratio value of 89.11%; 4) Based on the calculation of the Ratio of harmony between routine expenditure (operation) and development expenditure (capital) for the period of 2009 to 2016, there is a considerable disparity between the value of operating expenditure to capital expenditure. In that period, the average composition of operating expenditure from total expenditure was 81.25%, while capital expenditure was only 18.72%; and 5) Cumulatively, the financial growth ratio of North Sumatera province does not show stable growth. It does not reflect a definite purpose. The growth ratio of TPD, PAD and capital expenditures that should grow steadily towards an upward trend, to illustrate the good performance of local government in the effort to collect financial resources to finance regional expenditure, has not shown stable growth. From the calculation of first regression model analysis, it is known that all independent variables (independence ratio, effectiveness ratio, and efficiency ratio) have no significance value (P. value) ≤ 0.05. This means that the financial performance of North Sumatera Provincial Government (independence ratio, the effectiveness ratio and the efficiency ratio) has not significantly influenced the economic growth variable .Eeconomic growth variables have a significance value (P.value) of 0.666 or ≥ 0.05, which means that the economic growth of North Sumatra Province period of 2009 to 2016 has not significantly affected the unemployment rate variable.From the calculation of regression analysis of the third model, it is known that the variable economic growth has a value of significance (P.value) of 0.777 or ≥ 0.05, which means that the economic growth of North Sumatra Province period of 2009 to 2016 has not significant effect on the variable poverty level. Keywords : Evaluation, Regional Finance, North Sumatra Provincial Government